Using Blockchain Technology for Developing an Electronic Health Record of Emergency Ward: A Case Study of Galyanivadhanakarun Hospital - Jiamsawat, Watchara; Choksuchat, Chidchanok; Matayong, Sureena (Princess of Naradhiwas University Journal, 2021)
Using Blockchain technology for developing an Electronic Health Recordis intended to apply Blockchain technology to medical management in the emergency ward. This process is important because it is the first gate to pass patients through other medical care departments. This stage needs Data Integrity recordings and requires a high level of security. Existing internal desktop application systems could face the problem of the centralized database with weak security on a network. Therefore, this article aims to analyze the information transmission using blockchain through the peer-to-peer environment with monitoring on hash result. By verifying the data integrity based on the peer-to-peer network's hash function encryption method. This allows securely shared data between nodes and protected transactions over the network, which is also accurate in data transmission. We conducted a survey by using a sample of medical staffs which including 39 people of the nurse, pharmacists, patients, and physicians. The survey results showed that 50% of the survey participants were aware of the importance of patient health data, 52.94% strongly agreed about confidentiality and privacy on health information, and 44.12% strongly agreed that health data should be displayed correctly. 100% of the samples after testing the system confirmed that the represented data was completely accurate (X=5.00/5.00) and more than 40% of the sample group had a very good level (X=4.10-4.21/5.00) of satisfaction in all four areas.